FORMATION OF PEDAGOGICAL TACT OF THE FUTURE TEACHERS IN THE ART PROCESS DESIGNING - Fedorova, L.H. (Pedagogy of Higher and Secondary Education, 2006)
This article is about the questions of forming of pedagogical tact in the process of artistic constructing